Obituary for Jörg Huffschmid - John Grahl (Intervention. European Journal of Economics and Economic Policies, 2010)
First paragraph: The death of Jörg Huffschmid in December 2009, at the age of 69, is a loss to critical economics and to the movement for a more just and rational economic system. Jörg worked, in Germany and in Europe as a whole, both to develop a powerful critique of orthodox economic policies and to make that critique an effective instrument for the labour movement and the movements for environmental protection and sustainable development. This required an unusual combination of qualities: scholarship and keen analysis; the ability to persuade and convince in debate; the warmth and generosity which encouraged commitment to joint projects. Jörg was able to emphasize broad shared objectives even among those with intellectual and political differences.
Keywords: 330